PENGARUH PEOPLE, PROCESS, DAN PHYSICAL EVIDENCE TERHADAP KEPUASAN KONSUMEN DI MASA PANDEMI ( STUDI KASUS DI CAFE JANGKAR MOJOAGUNG ) - Karianto, Syerla Sylvia; Arifin, Muhyiddin Zainul; Fadhli, Khotim (JoEMS (Journal of Education and Management Studies), 2021)
The emergence of the Corona Virus (COVID-19) at the beginning of 2020 had a huge impact throughout Indonesia, especially for MSMEs, which experienced a decline in the midst of increasingly advanced world economic developments. Anchors café is one of the cafes in the Rejoslamet Mojoagung Jombang area, this café was established in 2020 and is a café whose ingredients are original ingredients from Indonesia. This study aims to determine the effect of People, Process and Physical Evidence on Consumer Satisfaction at Café Jangkar Mojoagung. This study is causal associative, namely to determine the effect or also the relationship between two or more variables. The sample in this study amounted to 100 obtained from consumer or customer data from Café Anchor. The data in this study were observed from the calculation of the questionnaires that had been distributed and interviews with the parties concerned. The results of the study indicate that there is an effect of People, Process and Physical Evidence together on Consumer Satisfaction at Café Jangkar Mojoagung. While partially, only People and Physical Evidence variables have an effect on Consumer Satisfaction, while the Process variable has no effect on Consumer Satisfaction.